Grid computing and biomolecular simulation. - Woods, C; Ng, M; Johnston, S; Murdock, SE; Wu, B; Tai, K; Fangohr, H; Jeffreys, P; Cox, S; Frey, J; Sansom, M; Essex, J (Royal Society, 2005)
Biomolecular computer simulations are now widely used not only in an academic setting to understand the fundamental role of molecular dynamics on biological function, but also in the industrial context to assist in drug design. In this paper, two applications of Grid computing to this area will be outlined. The first, involving the coupling of distributed computing resources to dedicated Beowulf clusters, is targeted at simulating protein conformational change using the Replica Exchange methodology. In the second, the rationale and design of a database of biomolecular simulation trajectories is described. Both applications illustrate the increasingly important role modern computational methods are playing in the life sciences.